2018
DOI: 10.1186/s12974-018-1131-7
|View full text |Cite
|
Sign up to set email alerts
|

Central blockade of NLRP3 reduces blood pressure via regulating inflammation microenvironment and neurohormonal excitation in salt-induced prehypertensive rats

Abstract: BackgroundInflammation has been implicated in the development of cardiovascular disease. We determined whether nod-like receptor with pyrin domain containing 3 (NLRP3) involved in the process of prehypertension, central blockade of NLRP3 decreased inflammation reaction, regulated neurohormonal excitation, and delayed the progression of prehypertension.MethodsPrehypertensive rats were induced by 8% salt diet. The rats on high-salt diet for 1 month were administered a specific NLRP3 blocker in the hypothalamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…A murine experimental hypertension model (uninephrectomy and treatment with deoxycorticosterone acetate and 0.9% NaCl in the drinking water) induced activation of the NLRP3 inflammasome in kidney and specific NLRP3 inhibitor, MCC950, inhibited the NLRP3 inflammasome and inflammation, resulting in improvement of hypertension in mice (78). In rats, salt-induced hypertension occurs partly due to the role of NLRP3 inflammasome activation in the hypothalamic paraventricular nucleus, while blockade of brain NLRP3 attenuates the hypertensive response (79). An absence of ASC also reduces pulmonary hypertension induced by hypoxia (80).…”
Section: Hypertension and The Nlrp3 Inflammasome In Pementioning
confidence: 99%
“…A murine experimental hypertension model (uninephrectomy and treatment with deoxycorticosterone acetate and 0.9% NaCl in the drinking water) induced activation of the NLRP3 inflammasome in kidney and specific NLRP3 inhibitor, MCC950, inhibited the NLRP3 inflammasome and inflammation, resulting in improvement of hypertension in mice (78). In rats, salt-induced hypertension occurs partly due to the role of NLRP3 inflammasome activation in the hypothalamic paraventricular nucleus, while blockade of brain NLRP3 attenuates the hypertensive response (79). An absence of ASC also reduces pulmonary hypertension induced by hypoxia (80).…”
Section: Hypertension and The Nlrp3 Inflammasome In Pementioning
confidence: 99%
“…In chronic inflammation, NLRP3 acts as the primary activator of inflammation, which can trigger the cascade production of other pro-inflammatory cytokines [50,51]. In salt-induced pre-hypertensive rats, NLRP3 inflammasome activation is associated with hypertension in the PVN [36,52]. We found that prorenin increased ROS production and triggered microglial M1 phenotype-switching and NLRP3 activation in primary cultured microglia.…”
Section: Discussionmentioning
confidence: 70%
“…4-pyridic acid was a metabolite of vitamin B6, and the low level of vitamin B6 was closely related to inflammatory status and cardiovascular mortality [50]. Gamma-aminobutyric acid, as an inhibitory neurotransmitter, has been found to be decreased in salt-sensitive hypertensive rats, and its increase decreased SHRs' blood pressure [51, 52]. Sphingosine 1-phosphate was catalyzed by sphingosine kinase (SPK) through the S1P receptor.…”
Section: Discussionmentioning
confidence: 99%